Responsive web design toolkit hammering websites into shape - Tabor, Ken (Focal Press, 2016)
Responsive Web Design Toolkit: Hammering Websites into Shape focuses on the nuts and bolts of responsive web design, showing you how to better build and how to debug websites that use the responsive technique. This book guides you through the technology that programmers use to build, test, and debug responsive websites